Effect of Organic Management on the Growth and Yield of Elephant Foot Yam - K, Venkatesan; P, Jansirani; R, Kamalkumar; R, Sujatha (JOURNAL OF ROOT CROPS, 2015)
The present investigation has been carried out to find the most suitable combination package of organic nutrition for growth, yield and quality of elephant foot yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) var Gajendra through AICRP on tuber crops scheme. The results of the experiment revealed that all the vegetative, yield and quality traits viz., plant height (74.44 cm), pseudostem girth (18.66 cm), canopy spread (E-W-58.24 cm), (N-S-48.96cm), corm yield (58.66 t/ha) and oxalic acid (102.40 mg / 100g) were found maximum with the treatment combination of recommended package of practices for conventional system FYM . 10 t/ha + 80:60:100 kg NPK/ha and using chemical pesticides. However, among the organic treatments, the highest plant height (72.56 cm), pseudostem girth (18.10 cm), canopy spread (E-W-56.40 cm), (N-S-48.00 cm), corm yield (57.84 t/ha) and oxalic acid (93.00mg/100g) were observed in the treatment combination of FYM (10t/ha) + Azospirillum (5kg/ha) + Phosphobacteria (5kg/ha) + Ash (5t/ ha).